دراسة بعض المؤشرات الكيميائية والفيزيائية والجرثومية والمحتوى من بعض المعادن الثقيلة في مياه نهر الكبير الشمالي وبئرين مجاورين له في منطقة الجنديرية - حماد ياسر; محمود اونج (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة على بعض المؤشرات الفيزيائية والكيميائية والجرثومية وبعض المعادن الثقيلة في مياه نهر الكبير الشمالي وبئرين مجاورين له في منطقة الجنديرية خلال فترة زمنية ممتدة من شباط 2008 وحتى كانون الثاني 2009. وكانت نتائج هذه التحاليل ضمن الحدود المسموح بها عالمياً WHO/EPA)) باستثناء التحليل الجرثومي للنهر. كما أظهرت النتائج تفوق مؤشرات التلوث الكيميائية والجرثومية في مياه النهر على البئرين مشيرة بذلك إلى أن التربة قد رشحت معظم هذه الملوثات قبل دخولها إلى طبقة المياه الجوفية؛ إذ وصل التعداد لبكتريا الكوليفورم للنهر شتاءً إلى 104x16 MPN/ 100 مل، كما تفوق البئر2 على البئر1 وسجل أعلى تعداد لبكتريا الكوليفورم له في حزيران (300) MPN/ 100 مل، أما من ناحية الإيشرشيا القولونية فلم نلحظ أي تواجد لها طوال مدة الدراسة في البئرين المدروسين مما يدل على أن مصدر بكتريا الكوليفورم في الآبار هو التربة وليس برازياً. كما وتؤكد النتائج زيادة تراكيز كل من النحاس والكادميوم في البئر1 بالمقارنة مع الموقعين الآخرين مما قد أثر سلباً في التعداد الكوليفورمي وسيادة جراثيم العصيات الزرق المعروفة بتحملها للمعادن الثقيلة. وعليه تنصح الدراسة بتعقيم مياه الآبار قبل استخدامها لأغراض الشرب بتركيز > 0.5 مغ/ل من الكلور. This study investigated some physico–chemical, bacteriological parameters, and some heavy metals in the water of Alkabeer Alshamali River and two neighboring wells in Aljindeiriya region in the period extended from February 2008 to January 2009. The results were within the allowed limits according to (WHO, USEPA) except for the river which had higher physico–chemical, bacteriological pollutants. This may suggest that soil and sediment filtered most of these pollutants before they entered the groundwater. The river had the highest account of total coliform bacteria (TC) (16X104) MPN/100 ml in winter. For borehole water samples, parameters were higher in well 2 and recorded the higher account for total coliform bacteria (300) MPN/100 ml in June. For Escherichia coli (EC (there were absence for the two studied tube-wells, that indicates that the source of the coliform bacteria is the soil and not fecal pollution. The results showed that the higher concentrations of copper and cadmium in well 1 were more than the other two locations, which play negative role to total coliform count. Therefore, the dominant bacteria were Pseudomonas aeruginosa which is known to tolerate high concentrations of heavy metals. The study suggests that water from the two tube-wells should be treated with concentration of free chlorine > 0.5 mg/l before use as drinking water